Pengaruh AI-Driven Personalized Financial Services dan Mobile Banking Security terhadap Continuance Intention dengan Customer Trust Sebagai Mediasi - Aimar Rafli Marzuki; Munawaroh Munawaroh; Ringga Sentagi Asa (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of AI-Driven Personalized Financial Services and Mobile Banking Security on Continuance Intention, with Customer Trust as a mediating variable, among Generation Z users of Bank Jago in Jabodetabek. This research employs a quantitative approach using a survey method and PLS-SEM analysis based on the Stimulus-Organism-Response framework. The sample consists of 300 respondents selected through purposive sampling and analyzed using SmartPLS. The results show that both stimulus variables have a positive and significant effect on Continuance Intention and Customer Trust, and Customer Trust has a positive and significant effect on Continuance Intention while partially mediating both relationships. AI-Driven Personalized Financial Services is the strongest predictor of trust, while Customer Trust is the strongest predictor of Continuance Intention, explaining 39.3% of its variance. These findings highlight the importance of AI-based personalization, security, and trust-building in sustaining neobank usage among Generation Z.